2019
DOI: 10.1111/jen.12671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leaf conditions and flight activity on the behaviour of Platypus quercivorus (Murayama) (Coleoptera: Platypodidae)

Abstract: The important role of semiochemicals in the interactions between plants and insects has been extensively investigated. The volatiles produced by oak trees are thought to attract the ambrosia beetle Platypus quercivorus (Murayama), which causes wilt disease in Quercus trees, resulting in widespread damage. In the present study, we hypothesized that (a) P. quercivorus is attracted to the leaf volatiles emitted by host trees and (b) the response of P. quercivorus to leaf volatiles is affected by flight. An experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Flight experiments were conducted at the room conditions similar to those used for the olfactory bioassays at 25 °C and 100 lux light intensity. As in our previous study (Pham et al, 2019), the objective of flight experiments was to observe the changes in behavioral responses of P. quercivorus to leaf volatiles caused by flight, and not to estimate the flight capacity of the beetle. Therefore, we did not set a rule for how long beetles were attached to the flight mill before detachment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Flight experiments were conducted at the room conditions similar to those used for the olfactory bioassays at 25 °C and 100 lux light intensity. As in our previous study (Pham et al, 2019), the objective of flight experiments was to observe the changes in behavioral responses of P. quercivorus to leaf volatiles caused by flight, and not to estimate the flight capacity of the beetle. Therefore, we did not set a rule for how long beetles were attached to the flight mill before detachment.…”
Section: Methodsmentioning
confidence: 99%
“…Newly emerged beetles were used on each day of the experiment, and different beetles were used to test the responses to each of the tree species. In our previous study, we conducted similar assays using flight mill and Y-tube olfactometer and showed that the handling of beetles, attachment to and detachment from the flight mill, did not affect the response of beetles to leaf volatiles (Pham et al, 2019). One or two individual seedlings were used for each tree species throughout the experiments.…”
Section: Olfactory Responses Of Platypus Quercivorus To Leaf Volatilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, X. glabratus is attracted to leaf volatiles of redbay and swamp bay but not by leaf volatiles of non-hosts, and this attraction occurs even if the tree is undamaged. This finding is not peculiar, as other wood borers, including bark and ambrosia beetles, may also be attracted to leaf volatiles from their host [ 47 , 48 ]. The profile of redbay leaf volatiles corresponds to the monoterpene portion of the wood volatiles that also contain highly attractive sesquiterpenes [ 38 ].…”
Section: Attractants For X Glabratusmentioning
confidence: 97%